The technological factors that influence the users’ satisfaction in e-government context: A case study in Jabatan Pengangkutan Jalan (JPJ) Bukit Katil / Nurul Ain Hayati Hasnan and Noor Amira Azman - Hasnan, Nurul Ain Hayati; Azman, Noor Amira (Faculty of Administrative Science and Policy Studies, 2014)
This study is carried out to determine the technological factors that influence user satisfaction in electronic government context. As systems and technologies are being enhanced and developed, the discussion on their usefulness and user satisfaction have been continuously debate by researchers, scholar and practitioners. Besides that, the major concern on user satisfaction in electronic government context, the factors that influencing user satisfaction are also important. Hence, this study was conducted to study whether Information System (IS) Facilities, (IS) Competency, (IS) Integration, (IS) Structure and user support having a significant relationship to the user’s satisfaction in egovernment context. Other than that, this study is attempted to recognize which of the following technological factors have the most significant influence to the user’s satisfaction in e-government context. From 150 entries level personnel, a random sample of 97 employees are selected and surveyed to identify the technological factors that influence user satisfaction in electronic government context. Through questionnaires, employees are asked to assess both their level of satisfaction with the technological factors of e-government. Data will be analysed in terms of statistical correlations between measured variables.